Papua New Guinea food price bulletin: May 2021 - International Food Policy Research Institute; Kedir Jemal, Mekamu; Schmidt, Emily (International Food Policy Research Institute, 2021)
During the first quarter of 2021, the International Food Research Institute (IFPRI) in collaboration with the Fresh Produce Development Agency (FPDA) and the National Research Institute (NRI) collaborated to update the tools used to collect important crop price information in food markets across the country. In addition, the team designed and piloted a new market vendor survey that will inform function and performance of fresh food markets, as well as identify challenges and opportunities for fresh food supply and logistics supply chain processes. Results of the first market vendor survey will be published in the 2nd quarter bulletin in July, 2021.